Monitoring displacement, strain, and acceleration of a steel railway bridge - Willy Barasa; Wimpie Agoeng Noegroho Aspar; Pariatmono Sukamdo; Dwi Agus Purnomo; Mulyadi Sinung Harjono; Muhammad Abi Berkah Nadi; Anton Adibroto (Ain Shams Engineering Journal, 2023)
An evaluation of the existing steel railway bridge is necessary to obtain information in supporting policymakers to decide further strategies of the railway bridge maintenance process. The reliability and durability of the existing steel railway bridge were monitored regularly by installing instrumentations on the bridge. The railway bridge characteristics were reviewed by implementing a structural health monitoring system (SHMS). The advantages of the SHMS include an early warning system for the railway bridge structure in order to avoid failures. The objective of this study is to evaluate and monitor conditions of the railway bridge structure. The results of the study explained the vertical deflection of the railway bridge, the stress distribution of the entire truss, and the frequency that happens during loadings. This paper discusses and provides a recommendation to solve problems for users and necessary action in practice. This paper may be used by practicing engineers and researchers.